Introduction of controlling in the enterprise in the new paradigm of management - Butenko, Daria (Management and Entrepreneurship: Trends of Development, 2018)
Purpose. Rationale for the introduction of controlling in the enterprise in a New management paradigm. Design/methodology/approach. The basic principles of the research are historical, systematic and comparative methods, method of analysis and synthesis. Findings. The new management paradigm shows that the companies that sell high-quality goods (services) receive the greatest profits. The profit of such companies is very high, but the risk is even higher, so the issue of controlling implementation as a management concept is necessary for them. Because analyzing the views of domestic and foreign scientists proved that controlling is a management concept that provides an opportunity for the company’s management to make effective management decisions in a changing environment. Research limitations/implications. The scientific significance of the work is to identify the main features inherent In the new paradigm of management, providing their own vision of the essence of the concept of controlling. As a conclusion the necessity of introduction of controlling system in the conditions of a New paradigm of management for the purpose of improvement of quality of production at the enterprises is given. Originality/value. Ukraine’s focus on European integration increases the need for domestic enterprises to constantly improve the quality of products and services in order to compete in the emerging market. That is why management needs to receive information about the company’s activities in real time to make effective management decisions. Ensuring this process is possible only if the introduction of a controlling system in management.